2009
DOI: 10.1590/s0100-879x2009001100018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of I-FISH and G-banding for the detection of chromosomal abnormalities during the evolution of myelodysplastic syndrome

Abstract: Myelodysplastic syndrome (MDS) patients with a normal karyotype constitute a heterogeneous group from a biological standpoint and their outcome is often unpredictable. Interphase fluorescence in situ hybridization (I-FISH) studies could increase the rate of detection of abnormalities, but previous reports in the literature have been contradictory. We performed I-FISH and conventional karyotyping (G-banding) on 50 MDS patients at diagnosis, after 6 and 12 months or at any time if a transformation to acute myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…15,[24][25][26] Former studies have already demonstrated that additional FISH analyses of bone marrow blood offer less or no further information if a sufficient banding analysis of at least 20 bone marrow metaphases is available, and that FISH provides only valuable additional impact, if a chromosome banding analysis is missing. 10,11,15,[24][25][26] In patients with a normal karyotype by chromosome banding, additional bone marrow FISH analyses seem to be useful to detect small clones or small deletions. 11,12 Without doubt, FISH cannot, and should not, replace chromosome banding analysis in general.…”
Section: Discussionmentioning
confidence: 99%
“…15,[24][25][26] Former studies have already demonstrated that additional FISH analyses of bone marrow blood offer less or no further information if a sufficient banding analysis of at least 20 bone marrow metaphases is available, and that FISH provides only valuable additional impact, if a chromosome banding analysis is missing. 10,11,15,[24][25][26] In patients with a normal karyotype by chromosome banding, additional bone marrow FISH analyses seem to be useful to detect small clones or small deletions. 11,12 Without doubt, FISH cannot, and should not, replace chromosome banding analysis in general.…”
Section: Discussionmentioning
confidence: 99%
“…4,31,32 However, several studies have compared FISH and conventional cytogenetic analysis at specific times during the development of the disease and most of them have established only a small advantage of FISH to detect chromosomal abnormalities; because, classical FISH is a targeted method, which allows only to identify the changes that are indicated by strictly defined molecular probes. 3,21,33 FISH was suggested to be used in selected cases where insufficient numbers of metaphases are available for Standard G-banding. 4,8,21,32 In our study, clonal chromosome abnormalities had an incidence of 44.80%.…”
Section: Discussionmentioning
confidence: 99%
“…3,21,33 FISH was suggested to be used in selected cases where insufficient numbers of metaphases are available for Standard G-banding. 4,8,21,32 In our study, clonal chromosome abnormalities had an incidence of 44.80%. Deletions within the long arm of chromosome 5 are the most frequent changes in MDS accounting for roughly 30% of abnormal cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional G‐Band karyotype analysis was performed on bone marrow cells . Briefly, cultures were established in RPMI 1640 medium (Gibco, Grand Island, NY, USA) containing 30% fetal calf serum.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%